Efeitos da tutoria por pares em comportamentos de uma criança com autismo em contexto escolar - Antochio, Ingrid (2024)
The Revised DSM-V characterizes autism by persistent deficits in social communication and social interaction that can manifest themselves in different contexts, such as social reciprocity, verbal and non-verbal communication and skills to initiate, maintain and understand relationships between others. All of these limitations exponentially harm the child's development in a social context, especially at school, as peers have little or no adequate repertoire to deal with behaviors that differ from those observed in most individuals. Given this demand, the present project sought to evaluate the effects of using structured social interaction situations with the support of peer tutoring on the appropriate and inappropriate social behaviors of a child diagnosed with ASD. Thirteen students with typical development and one student diagnosed with ASD participated in the research, all enrolled in the 1st year of Primary Education at a regular school in the interior of São Paulo. An ABAB-type reversal design was used in order to obtain the effects of the treatment on appropriate social skills in children with ASD and their classmates, who played the role of individual tutors, responsible for appropriate social interactions. Between the initial baseline and the first phase of treatment there was mentoring training with peers, with the aim of directing interactions between them, which corresponded to: staying with, playing with and talking to a friend (based on English, Goldstein, Shafer, & Kaczmarek, 1997). For data collection, 21 sessions were carried out using the field diary and a table to record behaviors as instruments, considering four dependent variables: asking for an object and responding according to the request made, obtaining the other's attention appropriately, waiting turn, and look in the direction of the person when they are speaking. There was an increase in the target student's responses in all variables, but these data were not fully generalized to external environments (outside the classroom). The results corroborate the scientific findings, but there is still a need for more research in this area in the Brazilian context with other types of samples.